Putting research data into context: Scholarly, professional, and educational approaches to curating data for reuse. Issue 1 (2014) - Faniel, Ixchel M.; Minor, David; Palmer, Carole L.
ABSTRACT: In this panel session we will discuss approaches to data curation for data reuse, with particular emphasis on the contextual information needed for reuse. We invite three panelists to present perspectives from communities that are 1) conducting scholarly research in the area of data reuse, 2) performing data curation and preservation work, and 3) educating information professionals. Given the shared interests among the three communities, one of the major objectives of the panel session is to deepen the engagement and connection among these groups. We have planned interaction with the audience to integrate the panelists' different perspectives and approaches, outline common objectives, and explore ways we might create a common agenda in the area of data curation for data reuse.